2017
DOI: 10.1371/journal.pone.0177845
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in hand dominance and functional asymmetry in older adults

Abstract: The aim of the study was to investigate fine motor performance and ascertain age-related changes in laterality between the dominant and non-dominant hand. A representative sample of 635 adults (144 males and 491 females) aged 50 years and over completed a test battery MLS (Motor Performance Series) to assess a broad range of hand functions. Functional asymmetry was observed in all four motor tests (postural tremor, aiming, tapping, and inserting long pins). Significant differences between the dominant and non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 63 publications
3
21
2
Order By: Relevance
“…Although gender differences in dexterity have been documented in childhood and young to middle adulthood, few studies have examined this issue in older adulthood. In contrast, recent findings by Sebastjan, Skrzek, Ignasiak, and Slawinska (2017) showed more decline in older females in tapping and peg inserting tasks. Another important issue is whether there are gender differences in manual dexterity decline in older adults.…”
Section: Introductioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Although gender differences in dexterity have been documented in childhood and young to middle adulthood, few studies have examined this issue in older adulthood. In contrast, recent findings by Sebastjan, Skrzek, Ignasiak, and Slawinska (2017) showed more decline in older females in tapping and peg inserting tasks. Another important issue is whether there are gender differences in manual dexterity decline in older adults.…”
Section: Introductioncontrasting
confidence: 68%
“…In the latter studies, more decline has been found in older males, as shown by longer time needed to manipulate pegs in the Purdue Pegboard tasks. In contrast, recent findings by Sebastjan, Skrzek, Ignasiak, and Slawinska (2017) showed more decline in older females in tapping and peg inserting tasks.…”
Section: Introductioncontrasting
confidence: 68%
“…Centrally, ageing has been related to impaired efficiency of feedback processing of sensory information to guide limb target control (Ribeiro and Olivera, 2007 ; Goble and Anguera, 2010 ). Age-related physiological and anatomical degenerative effects such as changes in motor unit size, properties, control and morphology as well as altered inputs from the nervous system, can lead to reduced neural control affecting fine motor performance (Erim et al, 1999 ; Hunter et al, 2016 ; Sebastjan et al, 2017 ). With age, motor units reduce in number and become larger in size (Larsson and Ansved, 1995 ; Ling et al, 2009 ; Hunter et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that dominant hand use is associated with fine motor skills. In addition, studies have shown that there are significant differences between dominant and non-dominant hand regarding asymmetry, the number of hits and the completion time (5). Strength of hand grip and motion perception are associated with muscle strength in the upper extremity.…”
Section: Introductionmentioning
confidence: 99%